EIF SME Access to Finance Index - Salome Gvetadze; Helmut Kraemer-Eis; Frank Lang; Dario Prencipe; Simone Signore; Wouter Torfs (European Investment Fund (EIF), 2018)
This EIF Working Paper outlines the methodology underlying the new EIF SME Access to Finance (ESAF) Index. This newly developed index aims at monitoring developments in SMEs' access to financial resources in the EU and is going to be periodically updated. It fills a gap as such an index does not exist. Composite indicators can be a useful tool in the policy maker's toolbox, as they are able to summarise a complex phenomenon in one summary statistics that is straightforward to track over time, or compare between countries. However, composite indicators also have the reputation of being black boxes. Therefore, we strive for transparency by motivating all methodological considerations made throughout the construction of the ESAF Index.
Keywords: 330